Spousal decision-making and agricultural investments: The relation between information asymmetries, risk preferences and investments in agricultural intensification in rural Uganda - Schenkel, Leonie (2020)
Agricultural productivity of smallholder farmers in Uganda is low, and only a small amount of farmers apply new technologies. The decision to adopt new techniques is made within the agrarian household, and therefore it is crucial to better understand intra-household decision-making processes. Inefficient household outcomes are partly due to limited cooperation within households. We use information asymmetry as a proxy for non-cooperative behaviour within the household. We study the relation between spousal information asymmetry levels and investments in more efficient agricultural production through the adoption of intensification practices, as measured in a survey with spouses in Northern and Western Uganda. While we expect to see a negative relation between information asymmetry and households’ investments, we did not find significant results. Besides information asymmetry, risk preferences play a major role in the adoption decision. Individuals have their own levels of risk aversion that potentially differ between spouses. We wanted to understand whose preference is decisive within the spousal bargaining process and tested the relation between investments in agricultural intensification and risk preferences, as measured in a Holt-Laury lottery. We hypothesised that the husband’s preference is taken more into account in the investment decision, and that risk aversion negatively relates to investments in agricultural intensification. Results did not show significance when measuring spousal categories with four risk categories, and did not show significance for husband’s preferences using round of switching as risk preference indicator. This last indicator, however, showed significance between wives’ switch round and husbands’ reported levels of investments in agricultural intensification, p<0.1. This suggests that wives’ risk preferences play a role in agricultural intensification, but in opposite direction from expected.